Effect of rubber bitumen interaction o the properties of dry mixed rubberized asphalt mixture - Bibi Farouk, Abdul Warith Ibrahim (2014)
The use of recycled scrap tires in asphalt mixtures is not a recent development with reclaimed tire crumb being used in the asphalt industry for over 40 years. Reclaimed tire crumb can be incorporated into asphalt mixtures using two different methods, referred to as the wet and dry processes. This study investigates the effect of rubber-bitumen interaction on the properties of rubberized asphalt mixture using dry process. The rubber-bitumen interaction is a significant issue in dry process even though this interaction is neglected in most of the previous studies. The =rubber swelling‘ activity occurs within the compacted asphalt mixture as a result of the bitumen absorption by the rubber particles that could result in inconsistent density of the compacted asphalt mixture, thus, affecting its performance. First, the effect of using different rubber gradation, bitumen content, and curing time on the interaction between rubber and bitumen or in other words the degree of bitumen absorption was investigated using =Basket Drainage Method‘. The investigation focused on the influence of these variables in achieving the target density as for rubberized asphalt mixture, it is important to achieve low target air void content after compaction for its stability. The relationships between the aforementioned variables and the target density of the mixture design were determined. An aggregate gradation of Asphalt Concrete with nominal maximum aggregate size 14 (AC14) was used for preparing the gyratory compacted samples modified with 2% crumb rubber with different rubber sizes. Finally these samples were tested for evaluating its performance in terms of dynamic creep and resilient modulus and compared with the conventional mixture. The results indicate a decrease in the resilient modulus and an increase in the dynamic creep for the rubberized asphalt mixtures. Fine rubber particles and the interaction time provided were observed to positively affect the mixture properties. Samples with fine rubber particles were found easily to compact compared to the one with coarse rubber.